Prevalence of diabetic retinopathy in Iran: a systematic review and Meta-analysis - Saman Maroufizadeh; Amir Almasi-Hashiani; Mostafa Hosseini; Mahdi Sepidarkish; Reza Omani Samani (International Journal of Ophthalmology, 2017)
AIM: To estimate the overall prevalence of diabetic retinopathy (DR) in Iran by a systematic review and Meta-analysis. METHODS: We conducted a search of all published literature on diabetic patients for the prevalence of DR using Web of Sciences, PubMed, Scopus, Google Scholar, and national electronic databases SID, Magiran, and Iranmedex from their inception until September 2016 with standard keywords. Pooled estimates of the DR prevalence and the corresponding 95% confidence intervals (CI) were calculated using random effects models. RESULTS: Thirty-one studies involving 23 729 patients with type I and II diabetes were included. The publication bias assumption for prevalence of DR was rejected by Begg and Egger tests (P=0.825, P=0.057, respectively). The results of Cochran test and I2 statistics showed considerable heterogeneity for prevalence of DR (Q=1278.21, d.f.=30, P<0.001 and I2=97.7%). The prevalence of DR, non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) in Iranian diabetic patients were 41.9% (95% CI: 35.6-48.2), 32.2% (95% CI: 28.7-35.8), and 13.2% (95% CI: 8.3-18.1), respectively. CONCLUSION: The prevalence of DR in Iran appears a little high. NPDR was more common. This study highlights the necessity for DR screening and management in diabetic patients in Iran.